Esthetic Rehabilitation of Anterior Teeth with Copy-Milled Restorations: A Report of Two Cases - Sapna Rani; Jyoti Devi; Chandan Jain; Parul Mutneja; Mahesh Verma (Case Reports in Dentistry)
Digitalization has become part and parcel of contemporary prosthodontics with the probability of most of the procedures being based on the digital techniques in the near future. This digital revolution started in the latter half of the 20th century by converting analog objects/signals into digital bits and bytes. Recent developments in all-ceramic materials and systems of computer-aided designing and computer-aided manufacturing (CAD/CAM), copy milling, and so forth offer excellent esthetics and superb biocompatibility. Copy milling system for ceramics enables milling of the zirconia cores of all-ceramic restorations precisely and also if this system is properly used the procedure for fabricating all-ceramic restorations can be substantially simplified. This case report presents fabrication of all-ceramic Maryland Bridge and post-core with a copy milling system for esthetics and preservation of integrity of tooth. For both of the patients, the use of biologic, all-ceramic, copy-milled restorations resulted in clinical success and recovered function and esthetics.